An overview of internet use among professionals of Moradabad: a critical appraisal - Priya, Neha; Khan, Samreen; Lal, Sachin (International Journal Of Community Medicine And Public Health, 2017)
Background: Internet is a boon and has certainly helped to bring the world closer. It has been a great medium for students to communicate and get information by transforming the academic landscape. However the excessive and undisciplined use of internet by individuals especially in the last decade, has led to the emergence of the concept of internet addiction. Therefore, a cross sectional study has been conducted to investigate the use of internet facility among undergraduate students from Teerthankar Mahaveer University using a validated questionnaire. There were about 42 million active internet users in urban India in 2008 when compared to 5 million in 2000. India now has the world’s third-largest national digital population, with approximately, 159 million Internet users in 2014, which is projected to reach 314 million by 2017 (IMRB 2014). The aim was to study prevalence and pattern of internet usage among undergraduate students in Moradabad. Methods: A cross sectional study was conducted among medical students (n=382) belonging to all the professionals of medical college, to assess the pattern of internet usage. A semi-structured proforma along with Young’s internet addiction scale was used. Results: Of the 382 adolescents who took part in the study, 150 (39.27%) were female and 232 (60.73%) were males. Their mean age was 16.20 years. Using Young’s original criteria, 22 (5.76%) were found to be addicts, 230 (60.21%) were moderately addicted, 45 (11.78%) were average users while in 85 (22.25%) of student’s internet use was less than average. Most of internet use was for social networking 183(47.9%), downloading media files 125 (32.7%), online gaming 45 (11.8%), academic purposes 10 (2.6%) and others 19 (5%). About 275 (72%) of the students were using smart phones to access the internet. Conclusions: Most of the internet usage was for the purpose of social networking (Facebook, Whats App, Mails, etc). Availability of high speed free wi-fi internet on mobile phones as well as more reliance on virtual friendship than real may be the reason for spending more time on social network websites.